A study into the impacts on retail operations performance of key strategic supply chain decisions. (18th December 2008) - Wanke, Peter F.; Arkader, Rebecca; Rodrigues, Alexandre M.
Based on a simulation methodology, this study aims at understanding and exemplifying the impact of key manufacturer production and distribution decisions on the key performance indicators in retail operations. More specifically, primary and secondary effects of alternative push/pull and centralisation/decentralisation inventory decisions on service level, average inventory, frequency of shipments and stock out indicators in retail operations are quantified by means of simulation of the operation of a simplified supply chain. Results of a MANCOVA analysis experimentally point out possible contradictions between the strategic positioning of manufacturing operations and retail operations performance.